Exploration of Teaching Reform in the Course of Biomass Development and Utilization - Xiaoxia YE; Qiu WU; Yuancai LV; Yifan LIU; Chunxiang LIN; Jie CHEN (Pige Kexue Yu Gongcheng)
"Development and Utilization of Biomass" is a core compulsory course in the major of Resource Cycle Science and Engineering, characterized by a broad knowledge base and strong practicality, making it an interdisciplinary course. In response to the issues present in traditional teaching, this paper proposed a student-centered, output-oriented, and continuous improvement teaching philosophy. A comprehensive reform of the teaching content, methods, and assessment has been implemented through the adoption of a "four-dimensional" blended learning approach. Research projects have been introduced, and a series of experiments closely related to the course content have been designed, including the modification and optimization of leather waste (collagen fiber membrane) for its utilization in emulsion separation. This included experimental procedures such as modification, characterization of the material’s structure and morphology, and testing of the emulsion separation performance. Experimental data was processed and analyzed using Origin software. These reform measures have not only enhanced the teaching quality of the course but also effectively promoted the improvement of students’ innovative abilities and overall qualities.